Tendências de pesquisa em Informação & Saúde no Brasil: análise do GT 11 do ENANCIB - Sampaio, Hibari Sebin (Universidade Federal de São Carlos, 2023)
With the growth of scientific production in health, the librarian's contribu-tion has proven to be indispensable for the treatment and availability of information in this area, in the face of the circulation of untrue infor-mation about health. From this perspective, information science plays a fundamental role in the creation and availability of informational products and services in the context of health that offer professionals in the field and citizens mechanisms capable of acting assertively. Therefore, the question arises what are the research trends in information and health in Brazil? In order to contribute to the subject, the objective is to outline the profile of the publications presented in GT11 in the last five editions of ENANCIB, through the following research activities: present the insertion of health in Brazilian information science; map the scientific production of GT11 for the years 2017, 2018, 2019, 2021 and 2022; and discuss the profile of scientific research in the field of information related to infor-mation and health, based on GT11. This is an exploratory and descriptive research, with a qualitative and quantitative approach to the data. As a result, there were a total of 65 publications presented in the period, dis-tributed across five investigative axes, presented by 116 authors from 33 public and private sector institutions; with emphasis on issues linked to health information policies. It is concluded that the investigative axis is active and offers important paths for establishing actions that promote and support health information, as a guarantee of personal, collective and global development.
Research trends in Information & Health in Brazil: analysis of ENANCIB GT 11
Keywords: Informação e saúde; ENANCIB; Ciência da Informação; Information and health; Information Science; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO::BIBLIOTECONOMIA